2017
DOI: 10.1111/etho.12175
|View full text |Cite
|
Sign up to set email alerts
|

Dinámicas Ocultas: Culture and Psy‐Sociality in Mexican Family Constellations Therapy

Abstract: This article takes the ethnographic case of Family Constellations therapy in Oaxaca, Mexico, to demonstrate how a nonnative therapeutic practice articulates with local cultural frameworks to foster novel forms of therapeutic experience and sociality. Family Constellations in Oaxaca promotes particular forms of what I call “psy‐sociality,” or sociality generated by globalizing psy concepts, diagnoses, and practices, which produce new sites for self‐work and subject‐formation, but also for jointly processing soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
9
0
5
Order By: Relevance
“…Psychospiritual development is a growing industry that overlaps with what has been called the ‘psychoboom’ in contemporary China (Huang 2014; Kuan 2015; Yang 2018). In this particular project, Pritzker attended numerous events, including both multiple-day workshops and evening ‘salons’ focused on helping participants—many of whom belonged to the rising middle class in China—connect to their inner child (Bradshaw 1990; Ivy 1993; Pritzker 2016) and guiding them through personal emotional struggles through family constellation therapy (Cohen 2006; Duncan 2017; Pritzker & Duncan 2019). 1 She also conducted interviews with upwards of eighty workshop participants and leaders, all of which were professionally transcribed by a native speaker and then analyzed.…”
Section: Methods and Analytical Orientationsmentioning
confidence: 99%
“…Psychospiritual development is a growing industry that overlaps with what has been called the ‘psychoboom’ in contemporary China (Huang 2014; Kuan 2015; Yang 2018). In this particular project, Pritzker attended numerous events, including both multiple-day workshops and evening ‘salons’ focused on helping participants—many of whom belonged to the rising middle class in China—connect to their inner child (Bradshaw 1990; Ivy 1993; Pritzker 2016) and guiding them through personal emotional struggles through family constellation therapy (Cohen 2006; Duncan 2017; Pritzker & Duncan 2019). 1 She also conducted interviews with upwards of eighty workshop participants and leaders, all of which were professionally transcribed by a native speaker and then analyzed.…”
Section: Methods and Analytical Orientationsmentioning
confidence: 99%
“…In the 1990s, FCT was created by Bert Hellinger, a German priest who spent 16 years with the South African Zulus where he learned their language, worldview, and the use of ancestral reverence. He later trained in psychoanalysis and other therapy models, eventually creating a modality that is rooted in family systems theory, incorporates the ancestral reverence of the South African Zulus, raises awareness of collective traumas and connection to the body, to bring healing of transgenerational traumas and conflicts (Cohen 2006;Duncan 2017;Longo-Lockspeiser 2018). In a family constellation, an individual addresses a current issue by connecting with the ancestral field to uncover trans-generational situations they are not aware of.…”
Section: Latinx-centric Modalitiesmentioning
confidence: 99%
“…The study found that family constellation seminars improved psychological functioning at eight and twelve-month follow ups. Because family constellations focus on the individual while still incorporating the family and utilizing important aspects of indigenous traditions, Duncan (2017) suggests that family constellation therapy is a better fit for Oaxaca, Mexico (an area with a significant and diverse indigenous population) than traditional forms of psychotherapy. Family constellation therapy promotes "a type of self-knowing by articulating with local cultural frameworks and forms of sociality that allows participants to work within the matrix of intergenerational familial life" (Duncan 2017, p. 491).…”
Section: Latinx-centric Modalitiesmentioning
confidence: 99%
“…También, Stiefel, Harris, Zollmann, (2002) expresan directamente que no está guiada por lógica o razonamiento, pues la técnica requiere una experiencia sensorial preconceptual, y considera al individuo conectado con planos espirituales superiores. La premisa principal de las CF se centra identificar lealtades inconscientes a nuestros antepasados, explicadas por dinámicas ocultas y conflictos transgeneracionales (Duncan, 2017). Dentro sus conceptos, existen nociones encontradas que corresponden a explicar el "enredo familiar" influido por un campo energético, siendo símil, al concepto de inconsciente colectivo (Salters, 2013).…”
Section: Concepción General O Filosofía Inherenteunclassified